Enhancing Mobile Robots with Arm Integration for Autonomous Navigation and Minimal Human Involvement - Nazar Emilov (Research Retrieval and Academic Letters, 2024)
Robotics provides a valuable platform for testing theories from developmental psychology and cognitive science, aiming not only to develop biologically inspired robots but also to enhance our understanding of human cognitive processes. This project, which integrates computer vision, robotics, and embedded systems, has demonstrated its potential to revolutionize multiple industries. The system comprises several key components: a Raspberry Pi, a camera module, a robotic arm with servo motors, a mobile platform, and a suite of computer vision algorithms. The Raspberry Pi serves as the robot’s central processor, handling image analysis, decision-making, and control of the robotic arm. The camera module captures real-time images of tomato plants, which are then processed by the computer vision algorithms on the Raspberry Pi. These algorithms identify ripe tomatoes through color segmentation, contour detection, and feature extraction. Additionally, reducing reliance on manual labor can minimize physical strain and health risks, improving workers’ quality of life. The social impact of this technology includes creating new job opportunities in the robotics, computer vision, and technology sectors, fostering innovation and economic growth in diverse fields